Advanced Strategies for End-Stage Heart Failure: Combining Regenerative Approaches with LVAD, a New Horizon? - Tseng, Cheyenne C. S.; Ramjankhan, Faiz Z.; de Jonge, Nicolaas; Chamuleau, Steven A. J. (Frontiers in Surgery, 2015)
Despite the improved treatment of cardiovascular diseases the population with end-stage heart failure is progressively growing. The scarcity of the gold standard therapy, heart transplantation, demands novel therapeutic approaches. For patients awaiting transplantation ventricular assist devices have been of great benefit on survival. To allow explantation of the assist device and obviate heart transplantation, sufficient and durable myocardial recovery is necessary. However, explant rates so far are low. Combining mechanical circulatory support with regenerative therapies such as cell(-based) therapy and biomaterials might give rise to improved long-term results. Although synergistic effects are suggested with mechanical support and stem cell therapy, evidence in both preclinical and clinical setting is lacking. This review focuses on advanced and innovative strategies for the treatment of end-stage heart failure and furthermore appraises clinical experience with combined strategies.